2019
DOI: 10.1109/access.2019.2918354
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cyberbullying on Social Media in the Big Data Era Using Machine Learning Algorithms: Review of Literature and Open Challenges

Abstract: Prior to the innovation of information communication technologies (ICT), social interactions evolved within small cultural boundaries such as geo spatial locations. The recent developments of communication technologies have considerably transcended the temporal and spatial limitations of traditional communications. These social technologies have created a revolution in user-generated information, online human networks, and rich human behavior-related data. However, the misuse of social technologies such as soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 110 publications
0
57
0
Order By: Relevance
“…Main focus and contribution of the current study was to provide systematic way to apply level of severity in cyberbullying behavioural text using multi-class classification. [ 81 ] and [ 82 ] worked in this area focusing on the binary classification and did not highlight the systematic procedure to go about detecting cyberbullying severity. Moreover, aim of our study was to compare well-known approaches that have been discussed in [ 48 ], rather than results from their datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Main focus and contribution of the current study was to provide systematic way to apply level of severity in cyberbullying behavioural text using multi-class classification. [ 81 ] and [ 82 ] worked in this area focusing on the binary classification and did not highlight the systematic procedure to go about detecting cyberbullying severity. Moreover, aim of our study was to compare well-known approaches that have been discussed in [ 48 ], rather than results from their datasets.…”
Section: Discussionmentioning
confidence: 99%
“…excluding other users from a group or conspiring against them), whereas men tend to use more threatening words. On the other hand, as pointed out by Can and Atlas (2019), social media information has provided interesting hints for a better understanding of the online user behaviors associated with cyberbullying [58]. They reported that posts with cyberbullying contents received comments more frequently and fewer likes per post than other posts [58].…”
Section: A Main Featuresmentioning
confidence: 96%
“…Therefore, ML algorithms could serve to early and automatically detect cyberbullying, and to foster intervention protocols' timely activation. In the last decade, researchers have tested a variety of ML techniques such as victims' sentiment informed analysis, textual, and semantic analysis, and user features' analysis (e.g., gender) [46,47,58,49]. Plus, these methods allowed to detect a variety of cyberbullying outcomes including binary classifications (e.g., being or not-being involved), role identification in cyberbullying dynamics and the severity of consequences [50,51,52].…”
Section: B Machine Learning and Cyberbullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need for an architecture that preserves the log privacy, provenance, and confidentiality along with scalability of edge node integration in an efficient fashion. The subsequent sections provide the detail of proposed scheme based on discovered solutions along with threat model and security requirements [49,50].…”
Section: Related Workmentioning
confidence: 99%